2013
DOI: 10.1620/tjem.230.49
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Disharmony Transiently Impairs Learning and Memory in the Mouse by Increasing Dynorphin A Levels in the Amygdala

Abstract: Occlusal disharmony sometimes causes not only stiffness of neck but also psychiatric depression, suggesting that the condition of oral cavity may affect the central nervous system. Dynorphin A is an endogenous opioid peptide that specifically binds the κ-opioid receptor and has a protective role against stress. Dynorphinergic nervous system is intensely distributed in the amygdala and hippocampus that are coping areas with stress. As a model of malocclusion, we placed dental resin on the molars to increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…14 These findings also corroborate to another study by Okihara, et al 7 (2014), which found a memory impairment accompanied by low number of neuron cells in the hippocampus after long-term soft diet. 7 Previous studies on mastication impaired animal models through tooth extraction 22 , 23 , bite-raise 24 , 25 and long-term soft diets 7 , 26 found that these aspects may alter hippocampus learning and memory function. Other studies also proved that impaired function of the hippocampus due to long-term soft diet could be improved by providing a hard diet.…”
Section: Discussionmentioning
confidence: 99%
“…14 These findings also corroborate to another study by Okihara, et al 7 (2014), which found a memory impairment accompanied by low number of neuron cells in the hippocampus after long-term soft diet. 7 Previous studies on mastication impaired animal models through tooth extraction 22 , 23 , bite-raise 24 , 25 and long-term soft diets 7 , 26 found that these aspects may alter hippocampus learning and memory function. Other studies also proved that impaired function of the hippocampus due to long-term soft diet could be improved by providing a hard diet.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the manufacturer’s information, the dynorphin A antiserum was specific to dynorphin A (100%), but not to dynorphin B (0%), β-endorphin (0%), α–neo-endorphin (0%), or leu-enkephalin (0%). Its specificity was also validated by the antigen absorption test by other laboratories ( Wakabayashi et al, 2010 ; Yamada et al, 2013 ).…”
Section: Methodsmentioning
confidence: 97%
“…Following this, the rats were euthanized. Blood (serum and plasma) and brain (hippocampus, prefrontal cortex, and amygdala) samples were collected, as described previously [25], then stored at −80°C until further analysis.…”
Section: Experimental Designmentioning
confidence: 99%